Condensate Fractionation Column: Design Variation Study by Simulation (Journal of Chemical Engineering, 2011)
This work aims to study the quality of three products of a fractionation column considering different design conditions of the column using natural gas condensate as column feed. The first design was on a single traditional distillation column whereas the consecutive studies were done by modifying the distillation column to yield the same quality of products. This study includes the details quality variation along with the variation of design. The whole simulation study and analysis was done on ASPENTM HYSYS 7.1. Keywords simulation; fractionation; distillation; ASPEN; design. DOI: 10.3329/jce.v25i0.7241Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.65-70